Aerobic exercise and LDL cholesterol response - Wisnesky, Carolina de Campos (2012)
To put emphasis in the physical exercises a determinant factor in the treatment of the dyslipidemia, the main objective of this study is to verify through literature revision the relationship between LDL cholesterol, specifically, and the aerobic exercises. To ascertain these were selected 19 articles from 1996 to 2003. The population of the articles selected represents 3050 individuals, including 50% of males, 11% of females and 37% of both males and females. The age range of both sexes is from 15 to 64 years old. The methods of evaluation used in the research were: blood chemical analysis, corporal composition, BMI, VO2 max test. By the analysis of these data we can conclude that the aerobic exercises actually develop positive reactions in the lipoprotein profile, however when associated with diet, produce more effects. These reactions were observed in all studied population, which means male and females, over weighted, athletic or sedentary. It will be necessary in the future studies to establish more clearly in what intensity and frequency these reactions occur in more satisfactory way.